A simple method to quantify follicle survival in cryopreserved human ovarian tissue. Issue 12 (25th October 2018) - Kristensen, S G; Liu, Q; Mamsen, L S; Greve, T; Pors, S E; Bjørn, A B; Ernst, E; Macklon, K T; Andersen, C Y
Abstract: STUDY QUESTION: Can follicle survival in frozen–thawed human ovarian tissue be quantified in situ using the dye Neutral Red (NR) to stain viable follicles specifically? SUMMARY ANSWER: A follicle survival rate within ovarian tissue can be calculated using NR followed by histological evaluation and evidence for a consistently high follicle survival in a series of ovarian tissue from 25 Danish girls and women undergoing ovarian tissue cryopreservation (OTC) was obtained. WHAT IS KNOWN ALREADY: Securing follicle survival in cryopreserved ovarian tissue is crucial for proper quality control when centers wish to implement OTC. The only established technique for validation of follicle survival is xenografting of thawed ovarian tissue to immunodeficient mice. However, this functional test is expensive, time consuming, requires animal facilities and only provides a qualitative—not quantitative—measure for follicle survival. STUDY DESIGN SIZE, DURATION: Quantification of follicle survival in human ovarian tissue donated from 30 girls and women having tissue cryopreserved for fertility preservation from 2000 to 2015 at the Laboratory of Reproductive Biology in Copenhagen, Denmark. PARTICIPANTS/MATERIALS, SETTING, METHODS: Cryopreserved ovarian cortex was donated from 25 girls and young women aged 10–36 years (mean age: 25 years) and the average storage time in liquid nitrogen was 9.1 ± 5.6 years, ranging from 1.6 to 17.9 years. In 12 of the cases, the ovarian tissue was collected from the local hospital and in the other 13 cases the ovarian tissue was transported on ice up to 6 h prior to freezing. Donated fresh ovarian surplus tissue was obtained from five women aged 23–34 years (mean age: 27 years). Ovarian tissues were chopped into small fragments and incubated in culture medium containing 50 mg/ml NR for 3–4 h. Fragments of ovarian tissue containing clearly NR-stained follicles were selected for counting, encapsulated in 4% agar and were processed for histology to calculate a follicular survival rate. MAIN RESULTS AND THE ROLE OF CHANCE: The mean follicle survival rate in the 25 patients after freezing and thawing was 84% ± 11 (mean ±SD), ranging from 50% to 98%. The high follicle survival rate in this clinical series of patients reflects a constant high-quality service performed in our center and confirms the robustness of the slow freezing protocol. No significant association between follicle survival rates and storage time was found using linear regression analysis, suggesting that storage in liquid nitrogen does not affect viability of the tissue. No significant association in follicle survival rates was found between ovarian tissues collected at the local hospital compared to tissues transported on ice prior to freezing, supporting that prolonged cooling does not seem to greatly affect the follicle survival. For the fresh ovarian tissue, the average follicle survival rate was 91% ± 5 (mean ± SD) in five patients, ranging from 81% to 95%. LIMITATIONS, REASONS FOR CAUTION: Even though the NR staining requires active incorporation of the dye, the test is merely a short in situ test that cannot completely replace the functional value of xenografting studies in which the integrity and developmental potential of the ovarian follicles are assessed. WIDER IMPLICATIONS OF THE FINDINGS: OTC is now being employed around the world but to date it has been difficult for centers to evaluate the effectiveness of their program and perform proper quality control. NR staining combined with histological evaluation is the first quantitative method to provide a survival rate for follicles in frozen–thawed human ovarian tissue and offer a valuable and easily applicable tool to validate the cryopreservation procedure when implementing OTC or as routine quality control for the overall freezing performance within tissue banking facilities. STUDY FUNDING/COMPETING INTEREST(S): The Research Pools of Rigshospitalet, the Danish Cancer Foundation, Dagmar Marshalls Foundation, and the Novo Nordic Foundation are thanked for having funded this study. The authors have no conflicts of interest.